2020
DOI: 10.1016/j.celrep.2020.107909
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into the SPRED1-Neurofibromin-KRAS Complex and Disruption of SPRED1-Neurofibromin Interaction by Oncogenic EGFR

Abstract: SUMMARY Sprouty-related, EVH1 domain-containing (SPRED) proteins negatively regulate RAS/mitogen-activated protein kinase (MAPK) signaling following growth factor stimulation. This inhibition of RAS is thought to occur primarily through SPRED1 binding and recruitment of neurofibromin, a RasGAP, to the plasma membrane. Here, we report the structure of neurofibromin (GTPase-activating protein [GAP]-related domain) complexed with SPRED1 (EVH1 domain) and KRAS. The structure provides insight into how th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 75 publications
(117 reference statements)
2
55
0
Order By: Relevance
“…Hence, effector activation and Ras inactivation appear to be tightly coupled. Furthermore, given the involvement of multiple protein interactions, several context-dependent regulation mechanisms are possible during these steps [34]. It can be concluded that, at least in this particular case, the plasma membrane is the major site of Ras activity.…”
Section: Ras In the Plasma Membranementioning
confidence: 99%
“…Hence, effector activation and Ras inactivation appear to be tightly coupled. Furthermore, given the involvement of multiple protein interactions, several context-dependent regulation mechanisms are possible during these steps [34]. It can be concluded that, at least in this particular case, the plasma membrane is the major site of Ras activity.…”
Section: Ras In the Plasma Membranementioning
confidence: 99%
“…Hence, effector activation and Ras inactivation appear to be tightly coupled. Furthermore, given the involvement of multiple protein interactions, several context-dependent regulation mechanisms are possible during these steps [33]. It can be concluded that, at least in this particular case, the plasma membrane is the major site of Ras activity.…”
Section: Ras In the Plasma Membranementioning
confidence: 99%
“…Neurofibromin translocation to the cell membrane enables its localization in proximity to Ras for possibly more efficient downregulation of Ras by its Ras-GAP activity. Recently, Yan et al (2020) [77] resolved the structure of a trimeric complex between the neurofibromin GRD, the Spred1-EVH1 domain, and K-Ras, allowing a precise analysis of the neurofibromin/Spred1 interface. This provided a rationale for the mutations observed in Legius syndrome and revealed mechanistic insights concerning K-Ras regulation.…”
Section: Plasma Membrane Localizationmentioning
confidence: 99%